The Influence of Financial Literacy and Financial Attitude on Investment Behavior: The Mediating Effect of Self-Control in Generation Z - Ahmad Cahyo Nugroho; Istiharini Istiharini (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The expansion of digital technology increases Generation Z’s involvement in financial markets, yet also elevates the risk of impulsive and speculative choices driven by behavioral biases. This study aims to evaluate the influence of financial literacy and financial attitude on investment behavior among Generation Z in Jakarta, while explicitly examining self-control as an intervening mechanism. Utilizing a quantitative approach with an explanatory research design, primary data were gathered through structured online questionnaires from 200 active investors selected via non-probability purposive sampling. Data processing was executed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) managed through SmartPLS. The empirical findings reveal that financial literacy and financial attitude exert direct, positive, and significant influences on self-control and investment behavior. Self-control serves as a vital psychological bridge that partially mediates both relationships, demonstrating that cognitive knowledge and positive mindsets are significantly optimized when channeled through personal self-discipline. These insights carry substantial practical implications for financial educators and policymakers, indicating that successful youth financial initiatives must look beyond mere conceptual knowledge by comprehensively redesigning educational frameworks to actively cultivate future-oriented mindsets and digital self-regulation techniques.